2020
DOI: 10.1016/j.ijid.2020.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tocilizumab on mortality and/or invasive mechanical ventilation requirement in a cohort of 206 COVID-19 patients

Abstract: Highlights No therapeutics have yet been proven effective for the treatment of severe illness caused by SARS-CoV-2. By neutralizing a key inflammatory factor in the cytokine release syndrome in COVID-19, tocilizumab (TCZ) can block the cytokine storm and reduce the severity of the disease. Our case-control study found that patients treated with TCZ had a lower index of mortality and/or invasive mechanical ventilation (IMV) requirement than patients without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 20 publications
2
37
1
1
Order By: Relevance
“…The significant improvement of hypoxaemia and decreased levels of inflammatory markers, such as leukocytosis, CRP and D-dimer indicate the efficacy. Most importantly, there was only one case of need for mechanical ventilation and there were no early deaths, which is consistent with literature review (17,18). Limitations of our study Our study had several limitations, including the small sample size, the lack of control groups, study design issues, the lack of appropriate follow-up.…”
Section: Findings Of Our Studysupporting
confidence: 79%
See 1 more Smart Citation
“…The significant improvement of hypoxaemia and decreased levels of inflammatory markers, such as leukocytosis, CRP and D-dimer indicate the efficacy. Most importantly, there was only one case of need for mechanical ventilation and there were no early deaths, which is consistent with literature review (17,18). Limitations of our study Our study had several limitations, including the small sample size, the lack of control groups, study design issues, the lack of appropriate follow-up.…”
Section: Findings Of Our Studysupporting
confidence: 79%
“…Regarding to Tocilizumab, Roche's phase III EMPACTA achieved its primary goal: patients with COVID-19 associated pneumonia who received Actemra/RoActemra plus standard of care were 44% less likely to progress to mechanical ventilation or death compared to patients who received placebo plus standard of care (log-rank p-value = 0.0348; HR (95% CI) = 0.56 (0.32, 0.97)) (10). Another study conducted on severe pneumonic patients revealed the superiority of tocilizumab treatment in reducing the risk of invasive ventilation and mortality in contrast to standard care (supplemental oxygen, hydroxycholoroquine, azithromycin, antiretrovirals, low-molecular weight heparin) (18). According to Parr (19), current trials could not show exact efficacy due to inherent limitations.…”
Section: Laboratory Findingsmentioning
confidence: 99%
“… IL-6 receptor antagonist Sarilumab, Tocilizumab Effective in reducing cytokine release syndrome (CRS) [172] . Use of tocilizumab in COVID-19 patients (n = 30) showed reduced mechanical ventilation [173] , [174] , [175] . GM-CSF antagonist Gimsilumab, TJ003234 Monoclonal antibodies act as an antagonist to GM-CSF.…”
Section: Virus Attachment Inhibitorsmentioning
confidence: 99%
“…Use of tocilizumab in COVID-19 patients (n = 30) showed reduced mechanical ventilation [173] , [174] , [175] .…”
Section: Virus Attachment Inhibitorsmentioning
confidence: 99%
“…The effect of Tocilizuman on mortality and/or invasive mechanical ventilation in 30 severe COVID-19 patients compared with those in 176 patients who were not treated with Tocilizumab. This retrospective case-control study revealed that treatment with Tocilizumab results in a considerably lower mortality rate and/or invasive mechanical ventilation ( Klopfenstein et al, 2020 ).…”
Section: Immunomodulatorsmentioning
confidence: 99%